Concussion History and Career Status Influence Performance on Baseline Assessments in Elite Football Players. (30th March 2019) - Cookinham, Brittani; Swank, Chad
Abstract: Objective: To determine if concussion history and career status is associated with neurocognitive performance in elite football players. Methods: The study design was a cross-sectional single assessment. Fifty-seven elite football players (age 29.39 ± 7.49 years) categorized as draft prospects, active professional players, and retired professional players were assessed on the Sport Concussion Assessment Tool – third edition (SCAT-3), in an outpatient therapy setting. Results: Common symptoms were the following: fatigue (45.6%), trouble falling asleep (35.1%), difficulty remembering (33.3%) and irritability (22.8%); 36.8% reported no symptoms. The low concussion (0–1) group reported fewer symptoms ( U = 608.50, p < .001), less symptom severity ( U = 598.00, p = −.001), and produced greater scores on the Standardized Assessment of Concussion (SAC) total scores compared to the multiple concussion (2+) group ( U = 253.00, p = .024), but no differences were observed on modified Balance Error Scoring System (m-BESS) scores ( U = 501.50, p = .066) on the Mann–Whitney U test. The Kruskal–Wallis test and post-hoc analysis indicated retired players were significantly different from draft prospects and current professional players for total symptom scores ( p < .001), total symptom severity ( p < .001), SAC total scores ( p = .030), and m-BESS ( p < .001). Conclusions: Concussion history and career status appear associated with total symptoms, symptom severity, performance on the SAC, and the m-BESS in elite football players. With this in mind, future research is recommended to determine longitudinal impact for elite football players.